THE RATIO OF INDICATORS OF FIGHTING IN SITUATIONS OF DIFFERENT LEVELS OF INTENSITY (Spectrum Journal of Innovation, Reforms and Development, 2023)
The article presents the analysis of training and competition fights of highly qualified taekwondo players.